Complex regional pain syndrome: A rare but potentially disabling complication of transradial cardiac catheterization. Issue 5 (30th May 2019) - Wiper, Andrew; Amoroso, Giovanni; Rao, Sunil; Nolan, James
Abstract: Background: Chronic Regional Pain Syndrome (CRPS) is a rare complication following transradial cardiac catheterization. Aims: To discuss the clinical features, pathophysiology, diagnosis and management of CRPS. Methods: Literature review performed. Results: CRPS is seen rarely in the literature following upper limb arterial access for coronary procedures, which may be due to a low incidence of the syndrome as well as limited recognition and underreporting. Discussion: The diagnosis and management of CRPS are discussed in detail. Conclusion: If CRPS is a potential diagnosis then prompt early referral to a center with a specialist interest in CRPS is recommended. Prompt diagnosis and early commencement on the correct patient treatment pathway are essential, to avoid potentially life changing disability and the psychological consequences of living with intractable chronic undiagnosed pain.